Atlas of Real Time 3D Transesophageal Echocardiography - Faletra, Francesco F.; Castro, Stefano; Pandian, Natesa G.; Kronzon, Itzhak; Nesser, Hans-Joachim.; Yen Ho, Siew.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
After almost three decades of research and clinical development, three-dimensional (3D) echocardiography has become a valuable tool in the diagnosis and management of cardiovascular disease. Current approaches achieve 3D imaging with the use of matrix array transducers that allow physicians to realistically visualize cardiac anatomy and pathology in real time. These advances have led to major improvements in the accuracy of chamber volumes and cardiac structure quantification, as well as in their functional analysis, while miniaturization of hardware has enabled a real-time 3D transesophageal transducer. This breakthrough technology delivers images of internal cardiac structures that are of vastly superior quality. The Atlas of 3D Transesophageal Echocardiography is intended to provide a comprehensive overview of the normal anatomy of the heart$1 (Bs interior structures as seen by this new revolutionary ultrasound technique. Normal cardiac structures obtained using 3D transesophageal echocardiography are presented and compared side-by-side with their corresponding anatomical specimens, focusing on both basic and detailed portrayals of the heart$1 (Bs anatomic structures and providing examples of the most common diseases. This atlas is therefore written not only for cardiologists specifically involved in the imaging of patients but also for general cardiologists, since it offers a wider view of normal and pathological cardiac anatomy.s
Technological Issues -- General Concepts -- The Mitral Valve -- The Aortic Valve and the Aorta -- Tricuspid and Pulmonic Valves -- Atrial and Ventricular Septa -- Right and Left Atria -- The Right Ventricle -- The Left Ventricle -- Clinical Cases.
Keywords: Medicine; Radiology, Medical; Cardiology; Medicine & Public Health; Cardiology; Diagnostic Radiology